Human Placental Trophoblasts Are Resistant to Trypanosoma cruzi Infection in a 3D-Culture Model of the Maternal-Fetal Interface - Silberstein, Erica; Kim, Kwang Sik; Acosta, David; Debrabant, Alain (Frontiers in Microbiology, 2021)
Trypanosoma cruzi (T. cruzi), the etiological agent of Chagas Disease (CD), is transmitted to humans by infected kissing bugs, blood transfusion, organ transplantation, and from mother-to-child. Congenital transmission is now considered an important route of CD spread in non-endemic countries where no routine testing of pregnant women for the disease is implemented. The main cellular mechanisms that lead to fetal infection by T. cruzi, despite the presence of a placental barrier, remain unclear. Mother-to-child transmission most likely occurs when bloodstream trypomastigotes reach the placental intervillous space and interact with the large cellular surface provided by the syncytioptrophoblasts. These highly specialized cells not only function as a physical obstacle between mother and fetus, but also modulate immune responses against pathogen infections. To overcome the limitations associated with the use of human fetal tissues, we employed a three-dimensional (3D) cell culture model to recreate the human placenta environment. In this system, the trophoblast-derived JEG-3 cell line is co-cultured with human brain microvascular endothelial cells attached to microcarrier beads in a rotating bioreactor. Here, we report that 3D culture of JEG-3/HBMEC spheroids promote JEG-3 cells differentiation revealed by the formation of syncytia and production of  human chorionic gonadotropin and human placental lactogen. Under these growth conditions, we demonstrate that 3D-grown JEG-3 cells have reduced susceptibility to T. cruzi infection compared to JEG-3 cells grown in conventional tissue culture flasks. We also show that 3D-cultured JEG-3 cells release paracrine factors in the supernatant that prevent T. cruzi infection of non-trophoblastic cell lines. Our in vitro model of T. cruzi vertical transmission may help better understand the molecular processes by which parasites bypass the human placental barrier and could be exploited to evaluate therapeutics to reduce congenital CD.